1996
DOI: 10.1042/bj3180029
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipoprotein lipase and apoprotein E in the recognition of chylomicrons and chylomicron remnants by cultured isolated mouse hepatocytes

Abstract: Lipoprotein lipase (LPL) has been proposed to play a role in the uptake of chylomicron remnants by hepatocytes by mediating the binding of these lipoproteins to cell-surface glycosaminoglycans and to the low-density-lipoprotein receptor-related protein (LRP). This proposal is based on studies that examined the binding of chylomicrons to HepG2 cells, fibroblasts and Chinese hamster ovary cells in culture, in the presence of large amounts of LPL [Beisiegel (1995) Curr. Opin. Lipidol. 6, 117-122]. We have investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…The cellular response of hepatic apoA-I mRNA elicited by the different diets points out that remnants are taken by the liver through an apoE-independent mechanism, as suggested by Chang et al [31][32] and Quarfordt et al 33 and poses an exciting question regarding the ligand that facilitates the uptake in these conditions. Induction of the hepatic transgene cholesterol ester transfer proteins expression in apoE-null mice in response to dietary cholesterol has been reported by MasucciMagoulas et al 34 Their results and ours clearly show that transcription machinery in animals lacking apoE ligand is sensitive to dietary manipulations.…”
Section: Discussionmentioning
confidence: 94%
“…The cellular response of hepatic apoA-I mRNA elicited by the different diets points out that remnants are taken by the liver through an apoE-independent mechanism, as suggested by Chang et al [31][32] and Quarfordt et al 33 and poses an exciting question regarding the ligand that facilitates the uptake in these conditions. Induction of the hepatic transgene cholesterol ester transfer proteins expression in apoE-null mice in response to dietary cholesterol has been reported by MasucciMagoulas et al 34 Their results and ours clearly show that transcription machinery in animals lacking apoE ligand is sensitive to dietary manipulations.…”
Section: Discussionmentioning
confidence: 94%
“…Although LPL is synthesized in extrahepatic tissues, it circulates in blood in association with lipoproteins and is cleared by the liver (45,46). Several studies have shown that LPL enhances the binding and uptake of lipoproteins by cultured hepatoma cells and hepatocytes (6,7,38) and enhances the uptake of lipoproteins and lipid emulsions in perfused rat livers (40). LPL can bind to at least three plasma membrane receptors (6): (i) heparan sulfate proteoglycans, the most abundant and widely expressed LPL-binding molecules present at the surfaces of most cells; (ii) the ␣2-macroglobulin receptor/ low-density lipoprotein receptor-related protein (LRP); and (iii) other members of the LDL receptor family, such as the LDL receptor, the VLDL receptor, and GP330/LRP2.…”
Section: Discussionmentioning
confidence: 99%
“…LPL is synthesized in extrahepatic tissues (27,37) and circulates in the blood in association with lipoproteins (45). LPL has been proposed to play an important role in the clearance of triacylglycerol-rich lipoproteins and chylomicron remnants by hepatocytes through bridging lipoproteins to cell surface receptors (6,7,38,46). In view of the in vivo biological relevance of LPL, we addressed the question of whether LPL could play a role as an extrahepatic carrier in bridging HBV virions to the cell surface during viral infection.…”
Section: Fig 2 Gst Pull-down Assays For the Verification Of Presmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of apoE-containing particles is mediated by HL [17], and in mice most plasma apoE is associated with HDL particles [17,18]. Other pathways in the modulation of plasma HDL levels are: cholesterol ester transfer protein (CETP)-mediated transfer of HDL cholesteryl esters to apoB-containing particles [19]; changes in the size and composition of HDL particles by the action of lechithin cholesterol acetyl transferase (LCAT) [20]; and uptake of whole HDL particles by a newly discovered HDL receptor, intrinsic factor vitamin B-12 receptor, also known as cubulin [21].…”
mentioning
confidence: 99%